Brain acid sphingomyelinase controls addiction-related behaviours in a sex-specific way - Liubov S. Kalinichenko; Iulia Zoicas; Anne-Marie Bienia; Clara Bühner; Julia Robinson; Joshua Kütemeyer; Annika Labonte; Thadshajiny Raveendran; Lena Warth; Irena Smaga; Malgorzata Filip; Volker Eulenburg; et al. (Neurobiology of Disease)
Addiction is a chronic and severe mental disorder with high gender- and sex-specificity. However, the pathogenesis of this disorder is not fully elucidated, and no targeted pharmacotherapy is available. A growing body of evidence points out the potential involvement of the ceramide system in the pathophysiology of addiction. A pathogenic pathway for several mental disorders based on the overexpression of an enzyme involved in ceramide formation, acid sphingomyelinase (ASM), was recently proposed. Here we show a crucial role of ASM specifically overexpressing in the forebrain for various types of addiction-related behaviours in a drug- and sex-specific way. In male mice, a forebrain ASM overexpression led to enhanced alcohol consumption in a free-choice paradigm. It also diminished the reinforcing properties of alcohol and cocaine, but not that of amphetamine, ketamine, or a natural reinforcer fat/carbohydrate-rich food in the conditioned place preference (CPP) test in males. In female mice, a forebrain ASM overexpression enhanced alcohol binge-like drinking, while moderate alcohol consumption was preserved. ASM overexpression in females contributed to CPP establishment for amphetamine, but not for other psychoactive substances. Altogether, this study shows a specific involvement of forebrain ASM in the development of conditioned reinforcing effects of different types of substances with addictive properties in a sex-specific way. Our data enlarge the current knowledge on the specific molecular mechanisms of dependence from various drugs of abuse and might serve as a basis for the development of drug- and sex-specific targeted therapy.